Uma nova estratégia analítica para a quantificação de cumarina em infusão de guaco utilizando voltametria de onda quadrada - Nóbrega, Denise Marques da (2020)
Medicinal plants and herbal medicines provide health benefits, but they are thought to be likely to cause side effects. The coumarin is adopted as a marker chemical for guaco (Mikania glomerata Spreng). It is one of the main responsible for the medicinal properties of the species, such as a bronchodilator, expectorant, and anti‐inflammatory. However, there is evidence of an association between its use and side effects including vomiting, diarrhea, hypertension. Besides, blood coagulation factors may be affected by the administration of coumarin. It is therefore extremely important to quantify them, as well as, to ensure its quality control to establish the effectiveness and safety of herbal medicines. The main analytical technique for the determination of coumarin recommended by the Brazilian Pharmacopeia is high performance liquid cromatography which uses mainly organic solvents that are hazardous to human health and environment, and besides, the instrument is expensive and time-consuming. Thus, in this work was developed a new electrochemical methodology for the determination of coumarin in an aqueous infusion of guaco by square wave voltammetry (SWV). Using cyclic and square wave voltammetry were observed an irreversible system controlled by diffusion with the oxidation peak potential recorded around + 1,77 V in Britton-Robinson buffer 0,1 mol L -1 , pH 10. The optimized SWV parameters were frequency 75 s-1 , pulse amplitude 75 mV, step potential 5 mV. The analytical curve was constructed in a linear range between 1,54 and 15,3 μg mL-1 , R2 = 0,9971. The limits of detection and quantification were 0,20 e 0,62 μg mL-1 , respectively. Analysis of Variance (ANOVA) (with 95% confidence level) confirms the significance of the regression model and conclude that there is no lack of fit. The coumarin was determined in an aqueous infusion of guaco samples by the proposed method; the results were compared to the reference method and they are not statistically significant. Further, the recovery values were around 85,85 to 107,62%. The coefficient of variation was ranged from 0,18 to 1,49% for repeatability. Additionally, the method developed was linear, accurate and precise; it required a simple sample pre-treatment that avoids organic solvents and laborious steps.